2007
DOI: 10.1111/j.1365-201x.2006.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat salivary gland ligation causes reversible secretory hypofunction

Abstract: Aim: To determine the influence of inflammation on salivary secretion. Secretion by salivary glands involves interactions between nerves, blood vessels and salivary cells. The present study investigated the effects of inflammation on rat submandibular gland function following acute ductal obstruction. Methods: Under recovery anaesthesia a metal clip was placed on the main duct of the submandibular gland. After 24 h salivary secretion was evoked by nerve and methacholine stimulation. For recovery experiments th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…Studies (10,15,31,49,81,89) of duct-ligated salivary glands have demonstrated a progressive atrophy of acinar cells, loss of saliva flow, and infiltration of immune cells within 24 h of ligation. Results from the current study demonstrate that BzATP perfusion of the main SMG excretory duct before a 24-h duct ligation induces significant immune cell infiltration, a response mediated by the P2X7R since it is absent in SMG of P2X7R Ϫ/Ϫ mice (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies (10,15,31,49,81,89) of duct-ligated salivary glands have demonstrated a progressive atrophy of acinar cells, loss of saliva flow, and infiltration of immune cells within 24 h of ligation. Results from the current study demonstrate that BzATP perfusion of the main SMG excretory duct before a 24-h duct ligation induces significant immune cell infiltration, a response mediated by the P2X7R since it is absent in SMG of P2X7R Ϫ/Ϫ mice (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The induction of acute salivary gland inflammation by ligation of the primary SMG excretory duct has been used by our group and others (2,10,15,31,49,81,89,98) for many years as an in vivo model of salivary gland dysfunction. Studies (10,15,31,49,81,89) of duct-ligated salivary glands have demonstrated a progressive atrophy of acinar cells, loss of saliva flow, and infiltration of immune cells within 24 h of ligation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of cholinergic and adrenergic innervation on IgA secretion has been reported at the intestinal level (Schmidt et al, 2007) and in the rat submandibular salivary gland Proctor, Carpenter et al, 2000;Proctor and Carpenter, 2002;Proctor et al, 2003a;Proctor et al, 2003b;Carpenter et al, 2004;Carpenter et al, 2005;Carpenter et al, 2007;Cox et al, 2007;Proctor and Carpenter, 2007). In the nasal mucosa, the cholinergic effect could have been enhanced by the adrenergic stimulation of the glands (Malm et al, 1983;Patow et al, 1984;Mullol et al, 1992;Morishita, 1995).…”
Section: Effects Of Acute Stress On Nasal Iga Levelsmentioning
confidence: 93%
“…In agreement with these results, it was described a decrease of saliva secretion in response to all types of secretagogues at early stages of inflammatory diseases. 41 Moreover, we have previously reported that endocannabinoids mediate salivary hypofunction after systemic inflammation, evaluated 3 h after of LPS injection. 28 In the present work, we evaluated the effect of LPS at shorter time (1 h) that was enough to increase TNFa glandular concentration, since the endotoxin was injected into the SMG, directly.…”
Section: Discussionmentioning
confidence: 99%